Tracing the prehistoric Nauportus: The hillfort on Tičnica hill near Vrhnika - Gaspari, Andrej; Masaryk, René (Arheološki vestnik, 2009)
Traces of a prehistoric fortified settlement on Tičnica hill near Vrhnika, discovered during a field survey in April 2009, are presented in this contribution. The hillfort comprises an irregular elliptical central part of the settle-ment with several levels of terraces and a summit plateau, as well as two larger yards, all together measuring 4.5 ha. Remains of defence structures include ramparts, which are mostly seen as sharp breaks of the outer terraces into the lower slopes. Based on isolated finds of hand-made pottery, the site can be roughly dated to the Bronze and Early Iron Ages. From the settlement, which rises about 50 m above the surrounding area, one of the crucial parts of the caravan route between the northern Adriatic and Central Europe could be controlled, as well as traffic on the navigable Ljubljanica River. Based on the location and size of the hillfort, which has no comparison in the surroundings of Vrhnika, it is almost beyond doubt that it was the central settlement in the area of the reported prehistoric predecessor of the Roman Nauportus.